A latent-class discrete-choice model of demand for economics electives: a case study on the challenge to increase enrollment. Issue 1 (2nd January 2018) - Dillingham, Reginald T.; Breffle, William S.; Kelly, Matthew C.
ABSTRACT: Increasing enrollment in undergraduate and graduate economics courses that focus on the natural world (natural resource, environmental, energy, and mineral economics) is important for preparing a work force capable of addressing complex environmental issues. This is especially challenging for smaller universities that want to offer diverse electives in economics. This study seeks to obtain information on the effects of course attributes and student characteristics on preferences for and probabilities to enroll in economics courses offered at Michigan Technological University. A discrete-choice experiment is used to elicit 723 students' stated preferences for eight different course attributes. A latent-class model is used to probabilistically group students into different preference classes. The cost-effective methods demonstrated in this study can be applied to any courses in any fields to inform course-level marketing efforts aimed at bolstering enrollment while addressing administrative budget constraints.